2020
DOI: 10.3390/w13010018
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Lasting Effects of Drought Stress at a Growth Stage on Soybean Evapotranspiration and Aboveground BIOMASS

Abstract: Quantifying the lasting effects of drought stress on crop growth is a theoretical basis for revealing agricultural drought risk mechanism and formulating adaptive irrigation strategies. Based on two-season pot experiments of soybean in the Huaibei Plain, quantitative responses of plant evapotranspiration and aboveground biomass at each growth stage from a drought were carried out. The results showed that drought stress at a certain stage of soybean not only significantly reduced the current evapotranspiration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 51 publications
(74 reference statements)
1
9
2
Order By: Relevance
“…However, the suppressed growth after a drought during the Fl-stage is consistent with our hypothesis and in line with other studies that reported the potentially irreversible negative effects on soybean in response to drought at the Fl-stage (Cui et al, 2021;Wang et al, 2022). This finding points out that soybean response to drought and recovery dynamics to achieve drought resilience is not necessarily dependent on the growth stage.…”
Section: Effect Of Drought At Different Growth Stages On Morphologica...supporting
confidence: 93%
“…However, the suppressed growth after a drought during the Fl-stage is consistent with our hypothesis and in line with other studies that reported the potentially irreversible negative effects on soybean in response to drought at the Fl-stage (Cui et al, 2021;Wang et al, 2022). This finding points out that soybean response to drought and recovery dynamics to achieve drought resilience is not necessarily dependent on the growth stage.…”
Section: Effect Of Drought At Different Growth Stages On Morphologica...supporting
confidence: 93%
“…Timing of the stress situation is also important to consider. For example, if a period of drought occurs early in the season, the plants can compensate for negative effects when more favorable conditions return ( Dong et al, 2019 ; Cui et al, 2020 ). In contrast, a period of stress at critical developmental phases can cause irreversible damage, leading to high crop productivity losses ( Wei et al, 2018 ; Dong et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Water deficit in rice plants is a limiting factor that can reduce yields up to 25.4% and affect root length as a strategy to deal with drought stress [97]. In some plants, water deficit inhibits flower formation [98,99]. The conclusion is that water deficit can inhibit flowering, increase the number of solutes and reduce yields in plants.…”
Section: Physiological Effects and Mechanismsmentioning
confidence: 99%